THE EFFECTIVENESS OF SNOWBALL THROWING METHOD IN LEARNING UNDERSTANDING THE MEANING OF TEXT EXPLANATION COMPLEX - Lulu'diah Sri Purwati; Teti Sobari (JLER (Journal of Language Education Research), 2021)
This research is motivated by the researcher's curiosity about the successful use of the snowball throwing method in understanding the meaning of complex explanatory text. The purpose of this study is to determine the level of success obtained in the use of the snowball throwing method in understanding the meaning of complex explanatory text. The formulation of the research problems are: 1) is there a difference between before using and after the snowball throwing method? 2) Is the snowball throwing learning method used successfully in learning to understand the meaning of the explanatory text? This study uses a quantitative research approach with data collection techniques, namely tests. Research Results The significance of the results is sig. 0.000 means <0. 05 Based on it can be concluded that there is a significant difference between learning to understand the meaning of complex explanatory text before and after the application of the snowball throwing method to students of class XI MIA 3. This research also shows that the snowball throwing learning method gets an average value. N-Gain in class XI MIA 3 is 57.3% or it can be interpreted as quite effective in learning to understand the meaning of complex explanatory text.